Karakteristik Ceo terhadap Penghindaran Pajak dan Kinerja Perusahaan - Ni Made Mega Abdi Utami; Made Ayu Dwijayanti; Ni Luh Putu Normadewi Abdi Pradnyani; I Dewa Agung Nanditiya Putra (AKUA: Jurnal Akuntansi dan Keuangan, 2026)
This study aims to examine the effect of CEO characteristics, namely family ownership status (Family CEO) and CEO tenure, on firm performance and tax avoidance in manufacturing companies listed on the Indonesia Stock Exchange (IDX) during the 2019–2023 period. Firm performance is measured using Return on Assets (ROA) and Tobin’s Q, while tax avoidance is proxied by the Effective Tax Rate (ETR). This study employs a quantitative approach using linear regression analysis on 77 firms selected through purposive sampling, resulting in a total of 385 firm-year observations. The results indicate that Family CEO has no significant effect on ROA or Tobin’s Q, suggesting that the presence of a CEO from the controlling family does not directly influence firm profitability or market valuation. In contrast, CEO tenure has a positive and significant effect on ROA, indicating that longer CEO tenure enhances managerial capability in improving firm profitability. However, CEO tenure does not have a significant effect on Tobin’s Q, implying that CEO tenure is not a primary consideration for investors in assessing firm value. In the tax avoidance model, Family CEO has a significant negative effect on ETR, indicating that firms led by family CEOs tend to engage in more aggressive tax avoidance practices. Meanwhile, CEO tenure shows a negative relationship with ETR, suggesting an increasing tendency toward tax avoidance as CEO tenure lengthens, although the effect is not statistically significant.